Evaluation of logistic processing to reduce cross-contamination of commercial broiler carcasses with Campylobacter spp. - Potturi-Venkata, Lakshmi Prasanna; Backert, Steffen; Vieira, Sergio; Oyarzabal, Omar A. (Journal of Food Protection, 2007)
Cross-contamination of broiler carcasses with Campylobacter is a large problem in food production. Here, we investigated whether the contamination of broilers carcasses from Campylobacter-negative flocks can be avoided by logistic scheduling during processing. For this purpose, fecal samples were collected from several commercial broiler flocks and enumerated for Campylobacter spp. Based on enumeration results, flocks were categorized as Campylobacter negative or Campylobacter positive. The schedule of processing included the testing of Campylobacter-positive flocks before or after the testing of Campylobacter-negative flocks. During processing, flocks were also sampled for Campylobacter spp. before and after chilling. Campylobacter strains were identified with multiplex PCR and analyzed for relatedness with pulsed-field gel electrophoresis. Our results show that Campylobacter-negative flocks were indeed contaminated with Campylobacter strains originating from previously processed Campylobacter-positive flocks. Campylobacter isolates collected from carcasses originating from different farms processed on the same day showed similar pulsed-field gel electrophoresis patterns, confirming cross-contamination. These findings suggest that a simple logistic processing schedule can preserve the Campylobacter-negative status of broiler carcasses and result in products with enhanced food safety. Copyright ©, International Association for Food Protection.
Created from Fastlane, Scopus look-up